Dynamics of Romantic Relationship Satisfaction in Long Distance Relationships: A Psychological Perspective - Geong, Evanjelina Agracia Tumi; Wedyorini, Endang (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Individuals in long-distance relationships (LDR) have many challenges in maintaining their relationships. Many admit that it is difficult to live to the point of questioning the certainty of the relationship. However, many have also succeeded in living long-distance relationships. In fact, although LDR couples rarely have direct contact, they also have the same level of romantic relationship satisfaction as those in geographically close relationships. This study aims to explore the description of romantic relationship satisfaction in individuals in long-distance relationships. The method used is a literature review based on a literature review of previous publications regarding romantic relationship satisfaction in individuals in long-distance relationships. This study then shows that in achieving relationship satisfaction in LDR couples, namely by utilizing technological assistance to communicate which is then used for self-disclosure to build trust and minimize uncertainty in the relationship. Romantic relationship satisfaction also has an impact on individual health. Individu yang menjalani hubungan jarak jauh (LDR) memiliki banyak tantangan untuk mempertahankan hubungannya. Banyak yang mengakui sulit menjalaninya hingga mempertanyakan kepastian hubungannya. Namun banyak juga yang berhasil dalam menjalani hubungan jarak jauh. Faktanya, meskipun pasangan LDR jarang melakukan kontak secara langsung, mereka juga memiliki tingkat kepuasan relasi romantis yang sama dengan mereka yang berada dalam hubungan yang dekat secara geografis. Penelitian ini bertujuan untuk mengeksplorasi terkait gambaran kepuasan relasi romantis pada individu yang menjalani long distance relationship. Metode yang digunakan adalah literature review berdasarkan kajian literatur publikasi-publikasi sebelumnya mengenai kepuasan relasi romantis pada individu yang menjalani long distance relationship. Penelitian ini kemudian menunjukkan bahwa dalam mencapai kepuasan hubungan dalam pasangan LDR yaitu dengan memanfaatkan bantuan teknologi untuk berkomunikasi yang selanjutnya digunakan untuk pengungkapan diri demi terbentuknya kepercayaan dan meminimalisir ketidakpastian dalam hubungan. Kepuasan relasi romantis juga berdampak pada kesehatan individu.